KAJIAN LAJU INFILTRASI DALAM HUBUNGANNYA DENGAN PERGERAKAN BAHAN LIAT PENYUSUN TUBUH TANAH BERBAHAN INDUK BATU LIAT DAN PASIR - Ajidirman Ajidirman (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2005)
A research about movement of clay materials of soil body compiler through mechanism infiltrate and soils permeability have been conducted. The Result of research show happened movement of clay materials of soil body compiler both of soil parent materials. The maximum rate of infiltration at the soil derived from parent materials of Clay stone reach 8,79 cm / hour and downhill at deepness 52 cm ( BW1 horizon ) with speed 1,71 cm / hour. Referring to that seen rate of infiltration to cause happened movement of clay materials with tendency increase from 33 % at A horizon, increased of become 44 % at Bw1 horizon. While at the soil derived from parent materials of Sand stone that its maximum rate of infiltration reach 8,59 cm / hour and downhill at deepness 145 cm and show the increasing of clays content according to deepness of horizon and soil at Ap horison have 22% of clay and increased of become 50 % at horison 2Bt2 . Key Words : Pergerakan bahan tanah, mekanisme infiltrasi, dan bahan induk tanah